Using the quad helix to treat bruxism in children: a clinical case (Research, Society and Development, 2023)
Objective: To present a treatment for bruxism in children using quad helix as an intraoral device based on a clinical case. Methodology: A case report. Results: At the end of the treatment, the presence of the quad helix afforded enough space for the eruption of the permanent teeth, as well as had changed the child’s occlusal pattern, deprogrammed the parafunctional habit, cultivated a functional muscle pattern, reduced hyperactivity, and completely relieved all painful symptomatology. Conclusion: The use of quad helix for 4 months, along with achieving its orthodontic function, proved capable of increasing the patient’s proprioception by enhancing the non-visible recognition of the spatial location of the mandible, deprogramming the child’s bruxism, and consequently eliminating all pain in the temporal and superficial masseter masticatory muscles.